Interaction of the Commissioner for Human Rights with specialized ombudsmen in the Republic of Kazakhstan - Issabekova, V.S.; Balgimbekova, G.U. (Bulletin of the Karaganda University “Law Series”, 2025)
The article discusses the problems of interaction between the Commissioner for Human Rights in the Republic of Kazakhstan and specialized ombudsmen. The study revealed the main shortcomings of the current legislation: the lack of a clear mechanism of coordination between ombudsman institutions; fragmentation of the system of registration of complaints; insufficient interaction with government agencies and fragmented reporting system. International practices were examined through a comparative study: countries such as Canada, Finland, the United Kingdom, Spain and the United Kingdom have a well-developed system of human rights protection and provide clear mechanisms for cooperation between ombudsmen. This includes legal regulation of the transfer of complaints, data exchange and joint inspections. After careful consideration, specific proposals have been made to amend the Law of the Republic of Kazakhstan “On the Ombudsman for Human Rights”. It is hereby proposed to amend the Law “On the Rights of the Child”, the Social Code, the Entrepreneurial Code of the Republic of Kazakhstan in order to improve the effectiveness of interaction between human rights institutions. In particular, the proposal is aimed at strengthening cooperation between ombudsmen, developing regulations for their joint inspections, introducing a mechanism for transferring appeals between them, as well as creating a single digital platform for automated review of complaints. The proposed changes are designed to increase transparency, improve accessibility and coordination of activities to protect the rights of citizens.